Managing Sacralities Competing and Converging Claims of Religious Heritage - van den Hemel, Ernst (Explorations in Heritage Studies, 2022)
What happens when religious sites, objects and practices become cultural heritage? What are--religious or secular--sources of expertise and authority that validate and regulate heritage sites, objects and practices? As cultural heritage becomes an increasingly popular and influential frame, these questions arise in diverse and challenging manners. The question who controls, manages, and frames religious heritage, and how, arises with particular urgency. Case studies from Denmark, the Netherlands, Poland, Portugal and the United Kingdom present an analysis of the paradoxes and challenges that arise when religious sites are transformed into heritage.